Patients' Satisfaction after Primary Health Care Centers' Integration with Ministry of Health Hospitals, Jeddah - Mashal Mesfer Alsayali; Abdullah Al-Sahafi; Najlaa Mandoura; Hassan Bin Usman Shah; Ola Akram Abdul Rashid; Khalid AlSharif; Amany Hamed Abo Zayed; Adel Ibrahim; Abdullah Al-Zahrani; Fatima Al-Garni; Mahmoud Madani Alali; Abdullah Al-Garni; et al. (Springer, 2019)
In today's competitive and media-influenced health care environment, resource utilization is driven by patient outcome. A key criterion to evaluate the quality of health care services is to assess patients' satisfaction. The objectives of this study were to compare patients' satisfaction in the first and last quarters after Primary Health Care Centers' (PHCCs) integration with Ministry of Health (MOH) hospitals in Jeddah, and to identify the factors contributing toward patient's satisfaction in first and last quarters. This cross-sectional study was conducted among patients visiting PHCCs in the first and last quarters. Randomly selected participants were interviewed using a validated closed-ended questionnaire, part of which also included modified Patient Satisfaction Questionnaire (PSQ18) with its subscales and standard cutoffs. Chi-squared test and multinomial logistic regression analysis were run to find the factors associated with satisfaction. The overall satisfaction in our study participants was 66.3% in the first quarter as compared with 83% in the last quarter. The mean scores of most PSQ18 subscales in the first and last quarters after the integration showed significant difference. Multinomial logistic regression analysis of the first quarter after integration showed three to fourfold increase in satisfaction of individuals who perceive an improvement in registration counters' load, cleanliness of centers, satisfaction with the staff's behavior, and ease in referral as compared with non-satisfaction [OR 3.60 (p = 0.018); OR 4.33 (p = 0.001); OR 2.47 (p = 0.055); and OR 4.45 (p = 0.005), respectively]. However, in the last quarter those satisfied with the staff's behavior (OR 2.48, p = 0.038), and dental facilities (OR 2.74, p = 0.043) had an odds ratio of ≥2. PHCCs integration with the hospitals is an effective strategy, which not only has improved functionality but has a significant effect on patient's satisfaction. Treating patients served by PHCCs integrated with hospitals is thus recommended.